2016
DOI: 10.1016/j.apmr.2015.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Rehospitalization After Traumatic Brain Injury: A Population-Based Study

Abstract: Rehospitalization after TBI is common. Factors associated with rehospitalization can inform long-term postdischarge planning. Findings also support examining causes for rehospitalization by age and sex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
46
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 27 publications
5
46
0
Order By: Relevance
“…Such inconsistency may be due to the variety in study timeframe and national healthcare policies between this study and ours. However, our study agreed with Saverino et al 19 that those who were male, older, had more severe injury and more comorbidities had significantly higher readmission rates over time.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Such inconsistency may be due to the variety in study timeframe and national healthcare policies between this study and ours. However, our study agreed with Saverino et al 19 that those who were male, older, had more severe injury and more comorbidities had significantly higher readmission rates over time.…”
Section: Discussionsupporting
confidence: 92%
“…Contradictorily, the Canadian population-based TBI study 19 found no sex differences in the number of rehospitalizations for the first year, even though women between 15 and 49 years old had 15% more rehospitalizations than men at the 3-year follow-up. Such inconsistency may be due to the variety in study timeframe and national healthcare policies between this study and ours.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…None of the studies analysed in this review compared the effect of VRT between sexes. Although it has been reported that females may be more vulnerable to concussions, studies investigating sex differences in recovery time remain limited and inconclusive 54. Further research is also required to determine the optimal time frame to begin VRT post concussion, as well as determining the prescription and progression patterns that provide the most effective recovery.…”
Section: Discussionmentioning
confidence: 99%
“…6 In general, research in this area to date has demonstrated rehospitalization to be a substantial problem that reflects a need for a more detailed understanding of the risk factors as well as proximal causes for return to the acute setting. Identifying key intervention points for the prevention of relapses is essential to permit more successful outcomes for TBI patients.…”
mentioning
confidence: 99%